Optimization Design of 3Z（Ⅱ） Planetary Gear Train based on Parallel Selected Genetic Algorithm - Zhang Qiang; Liu Zefeng (Jixie chuandong)
The optimization design method of 3Z（ Ⅱ） planetary gear train is studied. The multiple object optimization model,whose objective functions are the minimum of volume of gear train and the maximum of transmission efficiency is built. The constrained optimization is transformed into unconstrained optimization by penalty function,and a solution algorithm is proposed based on parallelism selection genetic algorithm（ GA）.The case shows,the proposed method can apply to the optimization methods of 3Z（ Ⅱ） planetary gear train and the optimization effects are noticeable. There is much for reference of this method to other optimization of planetary gear train.